2021
DOI: 10.14488/bjopm.2021.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corona virus outbreak on micro and small scale enterprise operation in southwest Ethiopia

Abstract: Goal: This examination is expected to survey the effect of COVID-19 for micro and small scale enterprise activity in southwest Ethiopia.Design / Methodology / Approach: The current study used the graphic exploration plan which includes 346 micro and small-scale enterprises. Enterprise proprietors, government authorities, and specialists were invited to answer self-administered questionnaires and information was also acquired from archive audit of different reports and exploration results zeroing. Results:The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As per Zelalem and Abebe (2021), the outbreaks of COVID-19 significantly harmed the enterprise supply chain by 48%. Furthermore, the results of their study statistically demonstrate that the cost of raw materials increased significantly as a result of a shortage in the market (i.e., 59% of the 346 micro and small businesses in southwest Ethiopia experienced a shortage of raw materials as a result of the quarantine measure).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per Zelalem and Abebe (2021), the outbreaks of COVID-19 significantly harmed the enterprise supply chain by 48%. Furthermore, the results of their study statistically demonstrate that the cost of raw materials increased significantly as a result of a shortage in the market (i.e., 59% of the 346 micro and small businesses in southwest Ethiopia experienced a shortage of raw materials as a result of the quarantine measure).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wilkinson (2020) indicates that due to COVID 19, 11.1 percent of working hours were lost in low-income countries in 2020 as opposed to 2019, which means the pandemic has had a significant effect on businesses' ability to retain employees. According to Zelalem and Abebe (2021), the average number of full-time workers has decreased by 27%. Bloom et al, (2021) conducted survey research on the impacts of COVID-19 on more than 2,500 US firms have found a significant negative sales impact, with an average loss of 29% in sales.…”
Section: Introductionmentioning
confidence: 99%